The influence of different geographical origins and grades on the flavor of Qingxiangxing Baijiu: An integrated analysis using descriptive sensory evaluation, GC×GC–MS, E-nose, and ICP-MS - Qiao Huang; Xianping Qiu; Tongwei Guan; Jianshen Yu; Yichen Mao; Yu Li; Yuan Rao; Hongguang Shang; Yanhui Zhao (Food Chemistry: X)
The origin and grade are the important factors that influence the flavor and price of Qingxiangxing Baijiu (QXB). As the grade increased, sensory differences and geographical differences become more pronounced. The aromas of floral, fruity, and sweet become more noticeable, while the acidity decreased. The different substances among three grades of QXB mainly focused on esters and alcohols. Correlation analysis indicated that the increase in the concentration of ester compounds was one of the reasons for the significant differences in floral, fruity, and sweet fragrances. Because of the higher concentration of acidic compounds in northern QXB, its acidic taste was more pronounced. Meanwhile, the esters and ketones in southern QXB accounted for a higher proportion, which made its floral and fruity fragrance more prominent. PLS-DA was more suitable for the classification of QXB based on grade and region. And the metal elements in QXB could be used for regional identification.